Revitalizing Hospitality Services: The Transformation of Mary Alston Hotel’s Reservation System of Trinity University of Asia - Caritos, Jade Anne L.; Ignacio, Mark Angelo M.; Maglipon, Melanny Krystyn B.; Patron, Ellan Justin C.; Utanes, EIvan Denzel C.; Llevado, Ma. Fe R.; Donor, Emilyn A.; Bunag, Ferdinand R. (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose – Online hotel reservation systems provide guests with the convenience of making bookings at any time, thereby greatly enhancing the registration process.   This abstract provided a concise summary of the system's design, development, and evaluation. The objective of this project was to create a customized web-based booking system for Mary Alston Hotel at Trinity University of Asia, with a primary focus on integrating different components smoothly and automating transaction processing.  Method – The project utilized the Agile technique to break it down into manageable steps, fostering active involvement and debate from stakeholders. Technology Utilization: The CSS attribute background image was employed to integrate images into links and other elements, hence boosting the system's visual attractiveness. Conclusion – The system underwent assessment using the ISO-25010:2010 instrument, with a specific focus on its effectiveness, reliability, ease of use, compatibility, and maintainability. The majority of users indicated a strong level of agreement on the system's compliance with evaluation requirements. Additionally, they also strengthen administrative capabilities. The use of Agile development approaches, CSS implementation, and thorough review processes improved the functionality and acceptance of this technology in the hospitality industry. Recommendation – The developer of the Hotel Reservation System suggested that Trinity University of Asia's Mary Alston Hotel should implement the system to improve operational efficiency, given the demonstrated favorable outcomes. Practical Implication – The practical significance of this project lies in the fact that implementing online reservation systems, along with Agile development methodologies and user-friendly design, can result in enhanced efficiency, improved customer experiences, and a competitive edge in the hospitality industry. Therefore, similar businesses must contemplate the adoption of these innovations.